Efficient gene transfer with pseudotyped recombinant adeno-associated viral vectors into human chronic myelogenous leukemia cells - Sellner, Leopold; Veldwijk, Marlon Romano; Kleinschmidt, Jürgen; Maier-Laufs, Stephanie; Topaly, Julian; Fruehauf, Stefan; Zeller, W. Jens; Wenz, Frederik (Leukemia and lymphoma, 2011)
Gene transfer into chronic myelogenous leukemia (CML) cells may become of relevance for overcoming therapy resistance. Single-stranded pseudotyped adeno-associated viruses of serotypes 2/1 to 2/6 (ssAAV2/1-ssAAV2/6) were screened on human CML cell lines and primary cells to determine gene transfer efficiency. Additionally, double-stranded self-complementary vectors (dsAAVs) were used to determine possible second-strand synthesis limitations. On human CML cell lines, ssAAV2/2 and ssAAV2/6 were most efficient. On primary cells, ssAAV2/6 proved significantly more efficient (4.1 ± 2.5% GFP+ cells, p = 0.011) than the other vectors (<1%). The transduction efficiency could be significantly increased (45.5 ± 13.4%) by using dsAAV2/6 vectors (p < 0.001 vs. ssAAV2/6). In these settings, our data suggest conversion of single- to double-stranded DNA and cell binding/entry as rate-limiting steps. Furthermore, gene transfer was observed in both late and earlier CML (progenitor) populations. For the first time, efficient AAV gene transfer into human CML cells could be shown, with the potential for future clinical application.